2000
DOI: 10.4319/lo.2000.45.7.1594
|View full text |Cite
|
Sign up to set email alerts
|

Motion of dinoflagellates in a simple shear flow

Abstract: Turbulence can be highly significant to dinoflagellates by affecting their swimming motion. We examined the effects of simple shear flow on swimming trajectories and orientations of two species of dinoflagellates Glenodinium foliaceum and Alexandrium catenella. In the absence of either shear or a cue that can cause directional motion, swimming orientations of both species were insignificantly different from random. Although cells of G. foliaceum maintained their random swimming orientations upon exposure to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 23 publications
2
67
0
1
Order By: Relevance
“…This offset does not occur for deterministic Jeffery orbits (figure 3g) and is, in fact, a hallmark of the competition between rotational diffusion and shear, previously observed in colloidal suspensions [51] and bacteria [10], which is usually expressed by the rotational Péclet number, Pe R ¼ S=D R . As confirmed by our observations, this offset is stronger at low flow rates ðPe R 1Þ A similar offset in peak orientation also occurred in a previous experiment that tested the response of dinoflagellates to shear rates characteristic of oceanic turbulence in a Couette flow [34]. In line with experiments conducted here at similarly low shear rates, many of the orientation distributions reported in that study were uniform.…”
supporting
confidence: 91%
“…This offset does not occur for deterministic Jeffery orbits (figure 3g) and is, in fact, a hallmark of the competition between rotational diffusion and shear, previously observed in colloidal suspensions [51] and bacteria [10], which is usually expressed by the rotational Péclet number, Pe R ¼ S=D R . As confirmed by our observations, this offset is stronger at low flow rates ðPe R 1Þ A similar offset in peak orientation also occurred in a previous experiment that tested the response of dinoflagellates to shear rates characteristic of oceanic turbulence in a Couette flow [34]. In line with experiments conducted here at similarly low shear rates, many of the orientation distributions reported in that study were uniform.…”
supporting
confidence: 91%
“…At low shears, cumulative effects of active cell behavior, such as chemotaxis, would enhance cell contacts and fertilization rate (Karp-Boss et al, 2000;Soghomonians et al, 2002;Smith et al, 2007). At high shears, near-cell (<20·m) hydrodynamics induce gametes to rotate, and disassociate, thus accelerating a decline in gamete encounters and fertilization rate (Kiørboe and Titelman, 1998).…”
Section: Fluid Motion Constrains Cell Motility At High Shearsmentioning
confidence: 99%
“…Specialized flow chambers, such as the Taylor-Couette apparatus (Bartok and Mason, 1957;Goldsmith and Marlow, 1972;Karp-Boss and Jumars, 1998;Ameer et al, 1999), cone-and-plate viscometer (Highgate and Whorlow, 1970;Solomon and Boger, 1998) and many types of microfabricated devices (Dellimore, 1976;Meng et al, 2005), have enabled studies of flow and particle interactions. Several results have shown that flow dominates behavior and cells are transported like passive particles (Rossman, 1937;Happel and Brenner, 1965;Shimeta et al, 1995;Karp-Boss et al, 2000;Dombrowski et al, 2004). Shear induced, for example, leukocyte tumbling under hydrodynamic conditions that typify the blood flow of mammalian arteries and veins (Cinamon et al, 2001;Goldsmith et al, 2001;Kadash et al, 2004).…”
Section: Fluid Motion and Single Cellsmentioning
confidence: 99%
“…In Kessler [32], the gyrotaxis effect in biflagellated swimming algae was described. Karp-Boss et al [33] demonstrated that the differences in drag forces between body and flagella lead to preferential alignment with the flow. Recent experiments suggest that rheotaxis may significantly affect the navigation of mammalian sperm cells [18,19].…”
Section: Introductionmentioning
confidence: 99%